Low-cost WC-HEA hard alloy cutter material and manufacturing method thereof

By using high-entropy alloy instead of Co as the binder, combined with mechanical alloying and SPS sintering technology, WC-HEA cemented carbide with high hardness, strong fracture toughness and excellent high-temperature resistance are prepared, which solves the problem of insufficient performance of existing WC-Co cemented carbide in high temperature and corrosion environments and reduces production costs.

CN119710416APending Publication Date: 2025-03-28DALIAN UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411852242.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

When used in corrosion or high temperature environments, the corrosion resistance and high temperature resistance are insufficient. Co is a rare resource, resulting in high costs, which limits the development and application of cemented carbide.

Method used

High entropy alloy (HEA) is used instead of Co as the binder, and WC-HEA cemented carbide is prepared by mechanical alloying method and SPS sintering technology, controlling the sintering temperature and pressure to achieve lattice distortion of the HEA binder phase, thereby improving the hardness and toughness of the material.

Benefits of technology

It has achieved low-cost production of WC-HEA cemented carbide, with a hardness of more than 2000HV, a KIC value of more than 12MPa·m1/2, excellent high-temperature resistance and significantly improved service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710416A_ABST
    Figure CN119710416A_ABST
Patent Text Reader

Abstract

The invention relates to a low-cost WC-HEA hard alloy cutter material and a manufacturing method thereof, and relates to the technical field of hard alloy cutter production. The alloy comprises the following chemical components in percentage by mass: 0.3%-3.0% of Al, 0.7%-6.0% of Co, 0.5%-6.0% of Cr, 0.5%-6.0% of Fe, 1.0%-12.0% of Ni, 0.01%-0.5% of V, less than or equal to 0.0035% of O and the balance of WC and inevitable impurities. According to the hard alloy cutter material manufactured through the method, the cost of the binder is lower than that of Co, the density of the binder is 11-15 g / cm < 3 >, the relative density is 0.96 or above, the hardness is 2000 HV or above, the fracture toughness KIC value is 12 MPa.m < 1 / 2 > or above, the hardness difference is smaller than or equal to 20 HV, and the fracture toughness KIC value difference is smaller than or equal to 0.5 MPa.m < 1 / 2 >; the oxidation resistance is excellent at the temperature of 800 DEG C or below, the thickness of a surface oxidation film is smaller than or equal to 100 nm, the performance is not reduced, the high-temperature hardness and fracture toughness are excellent, and the service life is obviously prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cemented carbide tool production, and in particular to a low-cost WC-HEA cemented carbide tool material and a manufacturing method thereof. Background Art

[0002] Cemented carbide has high hardness, strength, wear resistance and corrosion resistance. It is known as the "teeth of industry" and is used to manufacture cutting tools, knives and wear-resistant parts. It is widely used in military industry, aerospace, mechanical processing, metallurgy, oil drilling, mining tools, electronic communications, construction and other fields. Cemented carbide is generally a composite material prepared with carbides (WC, TiC, etc.) of high-hardness refractory metals as reinforcing phases and metals such as cobalt or nickel, molybdenum as bonding phases. Since Co has excellent wetting properties on WC, WC-Co cemented carbide with metal Co as bonding phase is the most widely used. However, Co has poor corrosion resistance and high temperature resistance. When parts made of WC-Co cemented carbide work under harsh environmental conditions such as corrosion or high temperature, it is difficult to meet the use requirements. Co is also a rare and important strategic resource with a high price. The above problems limit the development and application of WC-Co cemented carbide, and new binder materials are urgently needed to replace Co.

[0003] In 2004, Taiwan scholar Ye Junwei and British scholar Carter and others proposed the concept of high entropy alloy (HEA). High entropy alloy (HEA) is generally composed of several single principal elements to form a simple solid solution crystal structure, avoiding the formation of intermetallic compounds, and has high entropy effect in thermodynamics, slow diffusion effect in kinetics, lattice distortion effect in organizational structure, and cocktail effect in performance. Therefore, it is generally believed that it has high strength, high hardness, high temperature resistance, corrosion resistance, and oxidation resistance. Although high entropy alloys have the above-mentioned performance advantages, their manufacturing methods and performance stability are still immature. There are no reports on their large-scale mature applications, and there are not many studies on their use in the manufacture of cemented carbide materials. The main existing related technologies are as follows:

[0004] Cemented tungsten carbide alloy with high entropy alloy as binder and its preparation method, application number 201811409111.2, the high entropy alloy binder is made of metal powder Al, Fe, Cr, Co and Ni in equal molar ratio by mechanical alloying method ball milling, and then mixed with 75% to 95% WC powder by mechanical alloying method ball milling, vacuum discharge plasma sintering, sintering temperature 1000 to 1250 ℃, sintering pressure: 30 to 50 MPa, heating rate: 20 to 150 ℃ / min, tungsten carbide and each metal element powder particle size 0.4 to 75 μm. The obtained WC cemented carbide has a phase composition of HCP phase WC and M3W3C phase and M3W9C4 phase, where M is Fe, Co, Cr, Ni. There are 5μm to 50μm round or rod-shaped pores in the cemented carbide, and the alloy density is 11.2 to 13.45g / cm 3 , Vickers hardness is 1900HV~2800HV, more than double the hardness of traditional WC / Co cemented carbide, and the cost is lower. The invention only mentions that high entropy alloy as a binder can improve high temperature mechanical properties and corrosion resistance, and increase the service life of the tool.

[0005] A metal ceramic based on a new binder and its preparation method and application, application number 201910722025.5, is prepared by mixing TiC0.5N0.5, WC, AIFeNiCoCr, Mo and NbC in a certain proportion, adding WC carbide balls and anhydrous ethanol to ball-mill the powder, heating to 1500-1550℃, pressing and sintering. The invention has a density of 99%-100%, a Vickers hardness of 1600HV-1750HV, and a bending strength of 2000-2150MPa. The invention mentions that the AIFeNiCoCr binder is a high-entropy alloy, and Cr and Al can form an anti-oxidation layer on the surface of the metal ceramic, which improves the anti-oxidation performance of the metal ceramic, and has the advantages of high strength, good wear resistance, and good thermal stability.

[0006] An ultrafine tungsten carbide cemented carbide with a high entropy alloy as a binder phase and a preparation method thereof, application number 202010231670.X, the binder is a high entropy alloy of Co, Cr, Ni, Cμ, Fe with a molar ratio range of 1 to 1.5, its mass percentage is 5 to 30%, and the balance is WC. The process is ball milling powder, pre-pressing, annealing (temperature 300 to 500°C, holding time 10 to 30min), vacuum hot pressing sintering (sintering pressure 40 to 50MPa, sintering temperature 1200 to 1400°C, heating rate 10 to 30°C / min, holding time 10 to 30min), annealing (annealing temperature 350 to 600°C, holding time 20 to 60min). The hardness of the ultrafine tungsten carbide obtained is 19.89~25.25HV, and the fracture toughness KIC is 12.41~16.38MPa.m1 / 2 . Room temperature wear rate 2.15~4.46mm 3 / (Nm),500℃ wear rate 3.02~5.24mm 3 / (Nm). The manufacturing process requires two annealing steps, which complicates the process and increases the cost.

[0007] High entropy ceramic-bonded WC cemented carbide and its preparation method, application number 202210869715.5, is made of W, Ti, C powder, or Ti, C, WC powder or TiC, Ti, WC powder by ball milling, pre-pressing, and spark plasma sintering (sps), with a sintering pressure of 40MPa, a sintering temperature of 1600-1800℃, and a holding time of 10min. Hardness 18.8-22.68GPa, fracture toughness 6.7-8.3MPa·m 1 / 2 , relative density 98.5~99.78%. Adding 0.2~0.5mL of dispersant to every 10g of powder increases the cost and has poor fracture toughness.

[0008] A high-performance composite binder phase cemented carbide and its preparation method, application number 202410768909.5, with 2% to 8% Co a Cr b Fe c Ni d Cμ e The high entropy alloy and 2% to 4% Co metal composite dual-phase structure (a:b:c:d:e=0.4-0.6:0.5-1.3:0.7-1.5:0.7-1.2:0.3-0.6) are used as the bonding phase, and the balance is WC powder. It is prepared by two 1400℃ vacuum pressureless sintering processes. Its density exceeds 99.1%, the average grain size of WC is 250nm to 400nm, the Rockwell hardness is 91.0HRA to 93.2HRA, and the fracture toughness is 11.5MPa·m 1 / 2 ~13.2MPa·m 1 / 2 . The Co content is still relatively high and the cost is high.

[0009] It can be seen that there are not many studies on using high entropy alloys as binders to manufacture WC cemented carbides, and the high entropy alloy binder cemented carbides and manufacturing methods mentioned in the above-mentioned prior art have certain defects and the overall performance is not ideal. Summary of the invention

[0010] According to the technical problems raised above, a low-cost WC-HEA cemented carbide tool material and a manufacturing method thereof are provided. The tool material manufactured by the present invention has a hardness of more than 2000HV and a fracture toughness KIC value of 12MPa·m 1 / 2The relative density is above 0.96, the high temperature resistance is excellent, the service life is significantly improved, and the high entropy alloy is used instead of Co as a binder, which is lower in cost.

[0011] The technical means adopted by the present invention are as follows:

[0012] A low-cost WC-HEA cemented carbide tool material, the chemical composition of which is calculated by mass percentage as follows: Al: 0.3%-3.0%, Co: 0.7%-6.0%, Cr: 0.5%-6.0%, Fe: 0.5%-6.0%, Ni: 1.0%-12.0%, V: 0.01%-0.5%, O≤0.0035%, and the balance is WC and unavoidable impurities.

[0013] The following is a detailed description of the mechanism of action of each alloy component in the present invention, wherein the percentage symbol % represents the mass percentage:

[0014] WC: Hardness above 90HRA, melting point 2870℃, density 15.63g / cm 3 , hexagonal crystal structure is the hard phase skeleton in cemented carbide materials, which has the functions of support, high hardness and high wear resistance. 70% to 96% WC has a certain solubility in the binder phase and is not easy to form a brittle third phase, so as to obtain a cemented carbide material with excellent hardness and toughness matching.

[0015] Al: Pure Al has a very low hardness of 25HB, a melting point of 660°C, and a density of 2.70g / cm 3 , with a face-centered cubic structure and good atomic ductility, it is the most abundant metal element in the earth's crust. Al is a non-carbide-forming element, which has the functions of deoxidation and nitrogenation, grain refinement, and easy formation of oxide film on the surface, which improves the oxidation resistance and corrosion resistance, inhibits the surface oxidation of the workpiece, and improves the surface quality. 0.3% to 3.0% Al is mechanically alloyed with several other metals to form a high entropy alloy binder, which improves the strength and toughness matching of WC cemented carbide.

[0016] Co: Cobalt has a hardness of 125HB, a melting point of 1495°C, and a density of 8.9g / cm 3 , with a close-packed hexagonal crystal structure, high hardness, brittleness, and ferromagnetism. At high temperatures, cobalt can maintain high strength and has low thermal conductivity and electrical conductivity. 0.7% to 6.0% Co is mechanically alloyed with several other metals to form a high entropy alloy binder, which improves the strength and toughness matching of WC cemented carbide.

[0017] Cr: Chromium hardness 110HB, melting point 1907℃, density 7.2g / cm 3, body-centered cubic crystal structure (BCC), with good wear resistance, high temperature oxidation resistance and corrosion resistance, and good tempering stability. In the process of mechanical alloying of metal powders of the present invention, other metal atoms are dissolved as solute atoms into the BCC crystal structure of chromium with a content of 0.5% to 6.0%. When the lattice distortion energy is too high under sintering conditions, due to the difference in atomic size, the lattice of the HEA high entropy alloy binder phase in the WC-HEA cemented carbide product is distorted from the BCC structure to the FCC structure, and a material with excellent strength and toughness matching is obtained.

[0018] Fe: Iron hardness 50HB, melting point 1538℃, density 7.87g / cm 3 , body-centered cubic crystal structure (BCC), good plasticity and toughness, but low strength and hardness. At room temperature and pressure, iron is a body-centered cubic crystal structure, consisting of one iron atom and eight adjacent iron atoms. Under high temperature or high pressure conditions, it is a face-centered cubic crystal structure. 0.5% to 6.0% Fe is mechanically alloyed with several other metals to form a high-entropy alloy binder, which improves the strength and toughness matching of WC cemented carbide.

[0019] Ni: Nickel has a hardness of 80HB, a melting point of 1453℃, a density of 8.9g / cm3, a face-centered cubic crystal structure (FCC), high corrosion resistance, high temperature oxidation resistance, and good thermal stability. Ni is a non-carbide-forming element that can form an infinite solid solution with good strength and toughness. 1.0% to 12.0% Ni is mechanically alloyed with several other metals to form a high entropy alloy binder, which improves the strength and toughness matching of WC cemented carbide.

[0020] V: Vanadium has a hardness of 264HB, a melting point of 1917°C, and a density of 6.11g / cm 3 , face-centered cubic crystal structure (FCC), small atomic distance, relatively fixed atoms, high corrosion resistance, high temperature oxidation resistance, good thermal stability. Vanadium is a strong carbide-forming element, easy to form high-dispersion carbides, and strongly improve wear resistance. 0.01% to 0.5% Ni is mechanically alloyed with several other metals to form a high-entropy alloy binder, which improves the strength and toughness matching of WC cemented carbide.

[0021] O: Oxygen is a harmful element in the present invention, and the less its content, the better. When the oxygen content exceeds 0.0035%, it will form oxides with Al, causing Al segregation, reducing the Al content in the high entropy alloy binder formed by mechanical alloying, and failing to form a crystal structure with excellent strength and toughness matching after sintering, thereby reducing the comprehensive performance of WC cemented carbide.

[0022] The high entropy alloy binder formed by mechanical alloying of the above-mentioned metal single substances can wet the WC hard phase, has a low melting point and is easy to be sintered quickly at low temperature by the SPS method. The WC-HEA hard alloy produced by the SPS sintering method has good compactness and a relative density of more than 0.96. After SPS sintering, the HEA binder phase is transformed from a BCC structure to an FCC structure, so the binder not only plays a bonding role but also provides sufficient toughness, thereby obtaining excellent comprehensive performance of matching hardness and toughness. The high entropy alloy is less expensive to replace Co as a binder for WC hard alloy tool materials.

[0023] Specifically, the present invention also discloses a method for manufacturing the above-mentioned low-cost WC-HEA cemented carbide tool material, comprising the following steps:

[0024] Step 11, HEA binder powder preparation, weighing Al, Co, Cr, Fe, Ni, V, single substance powders based on the weight percentage of the elements in claim 1;

[0025] Step 12, dry-grinding the powder using a planetary high-energy ball mill, evacuating the ball mill and filling it with 99.99% argon as a protective atmosphere, and performing ball milling according to preset parameters;

[0026] The particle size of HEA powder after ball milling does not exceed 150μm, the microstructure is body-centered cubic structure, and the grain diameter does not exceed 400nm;

[0027] Step 21, manufacturing a mixed powder of HEA high entropy alloy binder and WC, wherein the mass percentage of HEA binder is 4% to 30% and the balance is WC powder;

[0028] Step 22, dry grinding for 20h to 40h using a planetary ball mill at a rotation speed of 250r / min to 300r / min, grinding for 1h to 2h, then stopping for more than 20min, then reversing the ball mill for 1h to 2h, and repeating this process;

[0029] Step 23, adding anhydrous ethanol and wet grinding for 2h to 10h, and vacuum drying the slurry after ball milling at 80°C to 100°C for more than 40h;

[0030] The particle size of the WC-HEA powder after ball milling is less than 150μm, and the phase composition is a WC phase with a hexagonal crystal structure and a HEA phase with a body-centered cubic structure, and the grain diameter does not exceed 400nm;

[0031] Step 31, sintering by SPS DC spark plasma equipment or hot pressing;

[0032] Step 32: After sintering, the cooling rate is 100°C to 200°C / min, and when the temperature is cooled to below 100°C, the pressure is released, the vacuum is removed, the film is demolded, and the film is processed.

[0033] Furthermore, in step 11, the particle size of each elemental powder does not exceed 150 μm.

[0034] Furthermore, in step 12, the ball-to-material ratio is 8 to 10:1, the rotation speed is 250 to 300 r / min, and the ball milling time is 30 to 60 h.

[0035] Furthermore, in step 21, the particle size of the HEA powder and the WC powder does not exceed 150 μm, and the purity is above 99.9%.

[0036] Furthermore, step 31 specifically includes the following parameter control: controlling the heating rate in two stages, the heating rate below 1000°C: 100°C~200°C / min, the heating rate above 1000°C: 50°C~100°C / min; heating to 1100°C~1400°C for sintering, the pressure is 20MPa~40MPa, and the insulation time is 5min~10min.

[0037] The present invention adopts a DC spark plasma sintering (SPS) method to directly apply mechanical pressure and DC discharge pulse current to powder particles. The current intensity is large, the heating rate is fast, and the pressure is large. The sintered particles are spontaneously heated and the particle surface is activated under the action of an instantaneous high temperature field, thereby achieving rapid densification. The heating and cooling rates are fast and the sintering time is short, which reduces the diffusion rate of W and C, hinders the dissolution-precipitation growth of WC grains, inhibits the growth of WC grains, and helps to refine WC grains and HEA phases. In the present invention, without adding a grain growth inhibitor, the WC grains are less than 500nm, reaching the ultrafine grain level. The segmented control of the heating rate can make the sintering temperature more uniform and stable, promote the lattice distortion of HEA, and transform the BCC solid solution to FCC. The different sizes of the atoms of each component in the HEA binder cause a certain offset in the lattice positions of the lattice. The sintering heating increases the atomic kinetic energy, causing the crystal structure to deviate from the ideal crystal lattice. The lattice deformation cannot maintain the original lattice structure, and lattice distortion occurs. This lattice distortion helps to improve the toughness of WC-HEA. At the same time, lattice distortion hinders dislocation movement. Combined with the solid solution strengthening effect of the components, HEA has higher hardness and strength, achieving a good match between hardness and toughness.

[0038] Compared with the prior art, the present invention has the following advantages:

[0039] The cemented carbide material manufactured according to the above chemical composition and process uses high entropy alloy instead of single metal such as Co or Ni as a binder, which is more cost-effective. At the same time, two mechanical alloying and SPS spark plasma sintering methods are used to control the process parameters such as ball milling time and speed, heating and cooling speed, sintering temperature and pressure to obtain a uniform mixed structure of hexagonal crystal structure WC phase + FCC crystal structure HEA binder phase, the maximum diameter of WC grains is ≤500nm, the average diameter is ≤300nm, the diameter of HEA phase grains is ≤50nm, the volume accounts for 5% to 28%, and its density is 11 to 15g / cm 3 , relative density above 0.96, hardness above 2000HV, fracture toughness KIC value 12MPa·m 1 / 2 Above, hardness difference ≤ 20HV, fracture toughness KIC value difference ≤ 0.5MPa·m 1 / 2 ; Excellent oxidation resistance below 800℃, surface oxide film thickness ≤100nm, unchanged structure, no performance degradation, excellent high temperature hardness and fracture toughness, significantly improved service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0041] Figure 1 This is a SEM microstructure image of the WC and HEA mixed powder of Example 7 of the present invention.

[0042] Figure 2 3 is an XRD phase structure analysis diagram of WC powder, HEA powder and mixed powder of Example 7 of the present invention.

[0043] Figure 3 This is a SEM microstructure image of the sintered WC-HEA cemented carbide tool material of Example 7 of the present invention.

[0044] Figure 4 This is an XRD phase structure analysis diagram of the sintered WC-HEA cemented carbide tool material of Example 7 of the present invention. DETAILED DESCRIPTION

[0045] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0046] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0048] Unless otherwise specifically stated, the relative arrangement of the parts and steps described in these embodiments, the numerical expressions and numerical values ​​do not limit the scope of the present invention. At the same time, it should be clear that, for ease of description, the sizes of the various parts shown in the drawings are not drawn according to the actual proportional relationship. The technology, methods and equipment known to ordinary technicians in the relevant field may not be discussed in detail, but in appropriate cases, the technology, methods and equipment should be regarded as part of the authorization specification. In all examples shown and discussed here, any specific value should be interpreted as merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values. It should be noted that similar numbers and letters represent similar items in the following drawings, so once an item is defined in one drawing, it does not need to be further discussed in subsequent drawings.

[0049] In the description of the present invention, it is necessary to understand that the directions or positional relationships indicated by directional words such as "front, back, up, down, left, right", "lateral, vertical, perpendicular, horizontal" and "top, bottom" are usually based on the directions or positional relationships shown in the drawings. They are only for the convenience of describing the present invention and simplifying the description. Unless otherwise specified, these directional words do not indicate or imply that the device or element referred to must have a specific direction or be constructed and operated in a specific direction. Therefore, they cannot be understood as limiting the scope of protection of the present invention: the directional words "inside and outside" refer to the inside and outside relative to the contours of each component itself.

[0050] A low-cost WC-HEA cemented carbide tool material, the chemical composition of which is calculated by mass percentage as follows: Al: 0.3%-3.0%, Co: 0.7%-6.0%, Cr: 0.5%-6.0%, Fe: 0.5%-6.0%, Ni: 1.0%-12.0%, V: 0.01%-0.5%, O≤0.0035%, and the balance is WC and unavoidable impurities.

[0051] A method for manufacturing a WC cemented carbide tool material using a high entropy alloy as a binder, specifically comprising the following steps:

[0052] 1) Preparation method of HEA binder powder:

[0053] Al, Co, Cr, Fe, Ni and V single-substance powders are respectively taken according to the mass ratio of (8-9): (17-19): (16-17): (17-18): (37-39): (1-2) and mixed evenly, and the particle size of each single-substance powder does not exceed 150 μm; the powders and grinding balls are added into the ball mill of a planetary high-energy ball mill for dry grinding, the material of the jar body and the grinding balls are both stainless steel, the ball mill is evacuated and filled with 99.99% argon as a protective atmosphere, the ball-to-material ratio is 8-10:1, the rotation speed is 250 r / min-300 r / min, and the ball milling time is 30 h-60 h; the HEA powder particle size after ball milling does not exceed 150 μm, the microstructure is a body-centered cubic structure, and the grain diameter does not exceed 400 nm.

[0054] 2) Preparation method of WC-HEA powder:

[0055] The HEA powder in 1) is uniformly mixed with WC powder with a particle size not exceeding 150 μm and a purity of more than 99.9%, wherein the mass percentage of the HEA binder is 4% to 30%, and the remainder is WC powder; the mixed powder is dry-milled in a planetary ball mill, with a ball-to-material ratio of 8 to 10:1, a rotation speed of 250 r / min to 300 r / min, and a ball milling dry milling time of 20 h to 40 h; in order to reduce the cold welding phenomenon of the alloy powder during high-energy ball milling, the machine is stopped for more than 20 min after each ball milling for 1 h to 2 h, and then the ball milling is reversed for 1 h to 2 h, and this is repeated; anhydrous ethanol is then added for wet milling for 2 h to 10 h, the ball-milled slurry is vacuum dried at 80° C. to 100° C. for more than 40 h, and the dried powder is sieved through a 100-mesh sieve to obtain a powder with a particle size less than 150 μm, and the phase composition of the ball-milled WC-HEA powder is a WC phase with a hexagonal crystal structure and a HEA phase with a body-centered cubic structure, and the grain diameter does not exceed 400 nm.

[0056] 3) Manufacturing method of WC-HEA cemented carbide:

[0057] The mixed powder is sintered by SPS DC spark plasma sintering equipment with a current intensity of 3000A to 4000A; the heating rate is controlled in two stages, the heating rate below 1000°C is 100°C to 200°C / min, and the heating rate above 1000°C is 50°C to 100°C / min; the temperature is raised to 1100°C to 1400°C for sintering, the pressure is 20MPa to 40MPa, and the time is 5min to 10min; the sintering is stopped after the holding time is over, the current is returned to zero, and the temperature is quickly cooled to below 100°C at 100°C to 200°C / min to release the pressure, remove the vacuum, demold, and process.

[0058] The finished product phase composition is a hexagonal crystal structure of WC phase and a face-centered cubic structure of HEA phase, the maximum diameter of WC grains is ≤500nm, the average diameter is ≤300nm, the HEA phase grain diameter is ≤50nm, and the volume accounts for 5% to 28%. The microstructure of the WC-HEA cemented carbide material prepared in Example 7 is as follows: Figure 3 As shown, the maximum diameter of WC grains is 478nm, the average diameter is 211nm, the maximum grain diameter of HEA phase is 45nm, and the HEA phase accounts for 14.6%; the phase analysis of WC-HEA cemented carbide material prepared in Example 7 is as follows Figure 4 As shown, it is a two-phase composition of a hexagonal crystal structure WC phase and a body-centered cubic structure HEA phase.

[0059] The present invention firstly adopts mechanical ball milling to prepare HEA powder. Under the process parameters in 1) above, the components in the alloy system diffuse disorderly, and the mixing entropy (ΔSmix) is very high, which has an absolute advantage in the competition with the mixing enthalpy (ΔHmix), greatly reducing the free energy ΔGmix of the alloy system, thereby forming HEA powder with a BCC solid solution structure. The ball milling time is 30 to 60 hours, ensuring sufficient diffusion alloying time to allow high entropy effect to occur between the components, and no alloying reaction occurs with WC. The HEA powder has a particle size of no more than 150 μm and a grain diameter of no more than 400 nm.

[0060] The mechanical ball milling method is still used to make WC-HEA powder. The ball milling time is 20h to 40h. After each ball milling for 1h, the machine is stopped for 20min, and then the ball milling is reversed for 1h. This is repeated to ensure diffusion alloying while avoiding cold welding of the alloy powder during high-energy ball milling, so that the microstructure and performance are uniform after sintering; anhydrous ethanol is added for wet milling for 2h to 10h, and the slurry after ball milling is vacuum dried at 80°C for more than 40h to ensure that the particle size of the WC-HEA powder is less than 150μm, and a WC phase with a uniform hexagonal crystal structure and a HEA phase with a body-centered cubic structure are obtained, and the grain diameter does not exceed 400nm.

[0061] The powder morphology prepared in Example 7 is as follows Figure 1As shown, the grain diameters are all less than 400 nm; the phase analysis of the WC powder, HEA binder powder and the mixed powder of the two prepared in Example 7 is as follows Figure 2 As shown, WC powder is a hexagonal crystal structure phase, HEA powder is a body-centered cubic structure phase, and the mixed powder is a two-phase product of a hexagonal crystal structure phase and a body-centered cubic structure phase.

[0062] The chemical composition design of the steel in the embodiment of the present invention is shown in Table 1, the manufacturing process of the embodiment is shown in Table 2, and the performance of the workpiece of the embodiment is shown in Table 3.

[0063] Table 1 Chemical composition

[0064]

[0065]

[0066] Table 2 Manufacturing process

[0067]

[0068] Table 3 Organization and properties

[0069]

[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A low-cost WC-HEA cemented carbide tool material, characterized in that: The chemical composition by weight percentage is: Al: 0.3% ~ 3.0%, Co: 0.7% ~ 6.0%, Cr: 0.5% ~ 6.0%, Fe: 0.5% ~ 6.0%, Ni: 1.0% ~ 12.0%, V: 0.01% ~ 0.5%, O ≤ 0.0035%, and the balance is WC and unavoidable impurities.

2. A method for preparing the low-cost WC-HEA cemented carbide tool material according to claim 1, characterized in that: The steps include: Step 11, HEA binder powder preparation, weighing Al, Co, Cr, Fe, Ni, V, single substance powders based on the weight percentage of the elements in claim 1; Step 12, dry-grinding the powder using a planetary high-energy ball mill, evacuating the ball mill and filling it with 99.99% argon as a protective atmosphere, and performing ball milling according to preset parameters; The particle size of HEA powder after ball milling does not exceed 150μm, the microstructure is body-centered cubic structure, and the grain diameter does not exceed 400nm; Step 21, manufacturing a HEA high entropy alloy binder and WC mixed powder, wherein the mass percentage of the HEA binder is 4% to 30%, and the balance is WC powder; Step 22, dry grinding for 20h to 40h using a planetary ball mill at a rotation speed of 250r / min to 300r / min, stopping the mill for a while after milling, and then reversing the milling for 1 to 2h, and repeating this process; Step 23, adding anhydrous ethanol and wet grinding for 2h to 10h, and vacuum drying the slurry after ball milling at 80°C to 100°C for more than 40h; The particle size of the WC-HEA powder after ball milling is less than 150μm, and the phase composition is a WC phase with a hexagonal crystal structure and a HEA phase with a body-centered cubic structure, and the grain diameter does not exceed 400nm; Step 31, sintering by SPS DC spark plasma equipment or hot pressing; Step 32, after sintering, cooling at a rate of 100°C to 200°C / min, cooling to below 100°C, releasing the pressure, removing the vacuum, demolding, and processing; Step 32, the sintered WC-HEA cemented carbide tool material is a uniform mixed structure of a WC phase with a hexagonal crystal structure and a HEA binder phase with a FCC crystal structure, the maximum diameter of the WC phase grains is ≤500nm, the average diameter is ≤300nm, the HEA phase grain diameter is ≤50nm, and the volume accounts for 5% to 28%.

3. The method according to claim 2, characterized in that In step 11, the particle size of each elemental powder does not exceed 150 μm.

4. The method according to claim 2, characterized in that: In step 12, the ball-to-material ratio is 8 to 10:1, the rotation speed is 250 to 300 r / min, and the ball milling time is 30 to 60 h.

5. The method according to claim 2, characterized in that: In step 21, the particle size of the HEA powder and the WC powder does not exceed 150 μm, and the purity is above 99.9%.

6. The method according to claim 2, characterized in that Step 31 specifically includes the following parameter control: controlling the heating rate in two stages: the heating rate below 1000°C: 100°C to 200°C / min, and the heating rate above 1000°C: 50°C to 100°C / min; The temperature is raised to 1100℃~1400℃ for sintering, the pressure is 20MPa~40MPa, and the holding time is 5min~10min.

Citation Information

Patent Citations

  • Hard tungsten carbide alloy taking high-entropy alloy as adhesive and preparation method thereof

    CN109161774A

  • Metal ceramic based on novel binder as well as preparation method and application thereof

    CN110484763A

  • Ultrafine tungsten carbide hard alloy with high-entropy alloy as binding phase and preparation method thereof

    CN111286664A

  • High-entropy ceramic-bonded WC cemented carbide and its preparation method

    CN115287516B

  • A high performance composite binder phase cemented carbide and preparation method thereof

    CN118326222B